1998
DOI: 10.14198/altern1998.6.5
|View full text |Cite
|
Sign up to set email alerts
|

El debate de lo público y lo privado en servicios sociales

Abstract: 1 debate sobre lo que debe ser una prestación realizada desde la Administración Pública o desde las entidades privadas, sean éstas de carácter lucrativo o no, no es nuevo, ni tampoco se va a acabar en los próximos años; somos de la opinión que acompañará durante mucho tiempo al todavía incompleto Sistema Público de Servicios Sociales. Pero lo que no podemos negar es que este tema siempre despierta un vivo interés, y estimo que cada vez se plantea con más virulencia, con más pasión que razón en los argumentos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The existence of a relationship between contracting out and the provision of social services first became apparent in the late 1990s, when it was observed that although social spending was expanding, in the long term, the Spanish economy was unable to finance such an extensive social protection system, in which the local government provided the majority of these services. In consequence, contracting out came to be viewed as an appropriate vehicle for the provision of social services (Medina-Tornero, 1998).…”
Section: Social Services In Spainmentioning
confidence: 99%
“…The existence of a relationship between contracting out and the provision of social services first became apparent in the late 1990s, when it was observed that although social spending was expanding, in the long term, the Spanish economy was unable to finance such an extensive social protection system, in which the local government provided the majority of these services. In consequence, contracting out came to be viewed as an appropriate vehicle for the provision of social services (Medina-Tornero, 1998).…”
Section: Social Services In Spainmentioning
confidence: 99%